Penerapan Augmented Reality pada Wuling Motors Menggunakan Mobile Sebagai Pendukung Promosi Penjualan - Phyta Rahima; Melati Rosanensi; Suriyati Suriyati (Target : Jurnal Manajemen Bisnis, 2021)
The software development methodology used in this research is sourced from Luther and has been modified by Sutopo. The multimedia development methodology consists of six stages, namely concept, design, material collection, assembly, testing, and distribution. These six stages do not have to be sequential in practice, they can switch positions. The results or outputs achieved are the production of an application that can be run on electronic media such as mobile or Smartphone. . For employees or sellers, it can make it easier to promote the latest product results on Wuling Motors